PENERAPAN KARAKTER DISIPLIN MELALUI PEMBIASAAN PADA SISWA KELAS II SD NEGERI 0909 HURISTAK - Ilahi, Afdhal; Siregar, Rolia; Safitri, Reviva (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2024)
Abstract This study aims to understand the implementation of discipline character through habituation among second-grade students at SD Negeri 0909 Huristak in the 2023/2024 academic year. The habituation program is designed to develop students' discipline in adhering to school rules, completing tasks, and taking responsibility for classroom cleanliness. The research method used is qualitative, involving interviews, observations, and documentation. The findings show very positive results: 85% of students arrive on time, 100% comply with uniform regulations, 100% demonstrate social responsibility by correcting peers who break rules, and 100% maintain cleanliness by disposing of trash properly. Additionally, 95% of students are disciplined in completing homework and assignments, 90% actively participate in evaluations and discussions, and 100% effectively carry out classroom cleaning duties. The impact of this habituation is highly positive on students' attitudes and behaviors, with 95% understanding the importance of classroom cleanliness and 85% actively participating in cleaning. Teachers play a crucial role in implementing effective discipline approaches. The quality of students' work and active participation indicate a good understanding of educational values. Ongoing efforts from teachers and parents are needed to ensure consistent and effective discipline. Overall, the implementation of discipline character through habituation has significantly improved students' attitudes and behaviors, with opportunities for further improvement. Keywords: Discipline Habituation, Discipline Character, students Abstrak Penelitian ini bertujuan mengetahui penerapan karakter disiplin melalui pembiasaan pada siswa kelas II SD Negeri 0909 Huristak tahun ajaran 2023/2024. Program pembiasaan ini mengembangkan kedisiplinan siswa dalam ketaatan tata tertib sekolah, penyelesaian tugas, dan tanggung jawab kebersihan kelas. Metode penelitian yang digunakan adalah kualitatif dengan wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan hasil yang sangat positif: 85% siswa datang tepat waktu, 100% mematuhi aturan seragam rapi, 100% menunjukkan tanggung jawab sosial dengan menegur teman yang melanggar, dan 100% menjaga kebersihan dengan membuang sampah pada tempatnya. Selain itu, 95% siswa disiplin mengerjakan PR dan tugas, 90% aktif dalam penilaian dan diskusi tugas, dan 100% melaksanakan piket kebersihan kelas dengan baik. Dampak pembiasaan ini sangat positif terhadap sikap dan perilaku siswa, dengan 95% memahami pentingnya kebersihan kelas dan 85% aktif membersihkannya. Guru berperan penting dalam menerapkan pendekatan efektif untuk disiplin. Kualitas pekerjaan siswa dan partisipasi aktif menunjukkan pemahaman baik terhadap nilai-nilai pendidikan. Upaya berkelanjutan dari guru dan orang tua diperlukan untuk memastikan disiplin yang konsisten dan efektif. Secara keseluruhan, penerapan karakter disiplin telah berhasil meningkatkan sikap dan perilaku siswa secara signifikan, dengan peluang untuk peningkatan lebih lanjut. Kata Kunci: Pembiasaan Disiplin, Karakter Disiplin, Peserta Didik